MENGGUGAT KEBHINEKAAN: RESPON INTELEKTUAL MUDA PROGRAM PASCASARJANA UNIVERSITAS ISLAM NEGERI RADEN FATAH PALEMBANG TERHADAP KEPEMIMPINAN NON MUSLIM - Izomidin, Izomidin (Wahana Akademika: Jurnal Studi Islam dan Sosial, 2018)
AbstractIn the Islamic intellectual tradition, there are three issues that are always discussed regarding political leadership within the state. First, the question of less worthy leaders (imÄmatul mafÅ«l). Secondly, the question of the immoral leader (imÄmatul fÄsiq). And third, the question of non-Muslim leaders (imÄmatul kÄfir). This dynamic becomes urgent to be studied, especially in the domain of non-Muslim leaders (imÄmatul kÄfir). The growing questions are: (1) What is the young intellectual response of UIN Raden Fatah Graduate for non-Muslim leadership?; (2) How does the strategic move to strengthen diversity by minimizing the non-Muslim leadership debate of young intellectual perspectives of Graduate UIN Raden Fatah Palembang ?. Both of them are effective, especially the contribution to build diversity that gives togetherness and peace in Indonesia. Being a subject of further study is mainly strengthening the concept of pluralist leadership. AbstrakDalam tradisi intelektual Islam, ada tiga persoalan yang selalu dibicarakan terkait kepemimpinan politik dalam negara. Pertama, soal pemimpin yang kurang layak (imÄmatul mafá¸Å«l). Kedua, soal pemimpin yang suka maksiat (imÄmatul fÄsiq). Dan ketiga, soal pemimpin non-Muslim (imÄmatul kÄfir). Dinamika tersebut menjadi urgen untuk ditelaah terutama dalam ranah pemimpin non-Muslim (imÄmatul kÄfir). Pertanyaan yang berkembang atas hal tersebut adalah (1) Bagaimana respon intelektual muda Pascasarjana UIN Raden Fatah atas kepemimpinan non muslim?; (2) Bagaimana langkah strategis mengokohkan kebhinekaan dengan meminimalisir perdebatan kepemimpinan non muslim perspektif intelektual muda Pascasarjana UIN Raden Fatah Palembang ?. Kedua nya berdaya guna terutama kontribusi dalam membangun kebhinekaan yang memberikan kebersamaan dan kedamaian di Indonesia. Menjadi bahan kajian lanjutan terutama penguatan konsep kepemimpinan yang pluralis.